2021
DOI: 10.1097/mpg.0000000000003069
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Feeding and Necrotizing Enterocolitis: Does Time of First Feeds and Rate of Advancement Matter?

Abstract: Objective: The aim of the study was to determine if time to initial enteral feeding (EF) and rate of advancement are associated with necrotizing enterocolitis (NEC) or death. Methods: Secondary analysis of prospectively collected data of very-lowbirth-weight infants (VLBWI: 400-1500 g) born in 26 NEOCOSUR centers between 2000 and 2014. Results: Among 12,387 VLBWI, 83.7% survived without NEC, 6.6% developed NEC and survived, and 9.6% had NEC and died or died without NEC (NEC/death). After risk adjustment, time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Suspending trophic feeding was associated with less NEC cases and NEC related death. [19] Findings in this study describes neonates who started trophic feeding had 5.89 times more likely to acquire NEC. Length of hospitalization was notably linked with NEC contributing of 3.28 times higher chances of acquiring NEC compared to neonates with less than a week length of stay in this study.…”
Section: Ethiopiamentioning
confidence: 67%
“…Suspending trophic feeding was associated with less NEC cases and NEC related death. [19] Findings in this study describes neonates who started trophic feeding had 5.89 times more likely to acquire NEC. Length of hospitalization was notably linked with NEC contributing of 3.28 times higher chances of acquiring NEC compared to neonates with less than a week length of stay in this study.…”
Section: Ethiopiamentioning
confidence: 67%
“…Initiation of trophic feeding was associated with an increase in the risk of developing NEC, and it was evidenced by findings from a referral and training center in East Azerbaijan Province of Islamic Republic of Iran, 37 , 38 in which delaying initiation was associated with less NEC and NEC associated death.…”
Section: Discussionmentioning
confidence: 96%
“…also found a predominance of early‐onset NEC occurring at a median age of 6 days. This may be due to rapid advancement of enteral feeds or an increased exposure to formula milk 23 . A Cochrane review (2021) showed slow advancement of feeds had no protective effect against NEC, but did not comment on timing 24 .…”
Section: Discussionmentioning
confidence: 99%